Dental sinus with parotid duct fistula: An unusual presentation - Shetty Naren; Pandey Ashok; Mokal Nitin (Indian Journal of Plastic Surgery)
Injury to the parotid duct is commonly missed which may lead to a fistula subsequently. An external duct fistula is distressing to the patient because of continuous dribble of saliva during mastication. Management of established duct fistula is controversial with a variety of methods both conservative and operative being reported in the literature, each having varying degrees of success. Reconstruction of the duct is not a good option because of its modest results. Internal diversion of the opening is an innovative, simple method to correct this problem. We report the successful use of this technique in a case of distal parotid duct fistula associated with apical root abscess of maxillary molars with cutaneous sinus-an unusual presentation, with a brief review of the literature on the management of parotid fistula.